2008
DOI: 10.1111/j.1440-1746.2007.05121.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL‐40 as a marker of disease activity and stricture formation in patients with Crohn's disease

Abstract: Patients with CD, particularly those with a stricture formation, have significantly higher levels of YKL-40. YKL-40 seems to be a useful marker of disease activity as well as stricture formation in patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…It is usually generated by neutrophils, macrophages and cancerous cells and has been shown to play a role in cell proliferation and differentiation, angiogenesis, inflammation and extracellular matrix remodeling 5) . Recent studies have shown that a high YKL-40 level is associated with an increased disease activity and poor prognosis in patients with cancer, ischemic cardiovascular disease, rheumatoid arthritis, diabetes, asthma, inflammatory bowel disease and hepatic fibrosis [6][7][8][9][10] . Moreover, a strong relationship between the YKL-40 level and endothelial dysfunction has recently been demonstrated, particularly in diabetic populations and individuals with a history of renal transplantation [11][12][13] .…”
Section: Endothelial Function Testmentioning
confidence: 99%
“…It is usually generated by neutrophils, macrophages and cancerous cells and has been shown to play a role in cell proliferation and differentiation, angiogenesis, inflammation and extracellular matrix remodeling 5) . Recent studies have shown that a high YKL-40 level is associated with an increased disease activity and poor prognosis in patients with cancer, ischemic cardiovascular disease, rheumatoid arthritis, diabetes, asthma, inflammatory bowel disease and hepatic fibrosis [6][7][8][9][10] . Moreover, a strong relationship between the YKL-40 level and endothelial dysfunction has recently been demonstrated, particularly in diabetic populations and individuals with a history of renal transplantation [11][12][13] .…”
Section: Endothelial Function Testmentioning
confidence: 99%
“…31 Serum levels of YKL-40, which is released by activated macrophages and neutrophils and promotes myofibroblast-induced collagen secretion, are higher in the serum of Crohn's disease patients than in control subjects. 33,34 However, the comparison of serum YKL-40 between stricturing and unstricturing phenotypes produced contradictory results in two studies. 33,34 In keeping with the pro-angiogenic and pro-fibrogenic role played in liver fibrosis, 2 VEGF is increased in the serum of Crohn's disease patients 31,32 and also correlates with colour Doppler signal intensity, leading to the consideration of VEGF as biomarker of angiogenesis in Crohn's disease.…”
Section: Growth Factorsmentioning
confidence: 99%
“…33,34 However, the comparison of serum YKL-40 between stricturing and unstricturing phenotypes produced contradictory results in two studies. 33,34 In keeping with the pro-angiogenic and pro-fibrogenic role played in liver fibrosis, 2 VEGF is increased in the serum of Crohn's disease patients 31,32 and also correlates with colour Doppler signal intensity, leading to the consideration of VEGF as biomarker of angiogenesis in Crohn's disease. 32 Similarly, the pro-fibrogenic/proangiogenic PDGF, which is able to increase the production of collagen but not that of TIMP-1, is high in the serum of IBD patients.…”
Section: Growth Factorsmentioning
confidence: 99%
“…YKL-40 has been reported to be a marker for liver fibrosis [57]. It is also increased when intestinal strictures are present, but the correlation coefficient is only r = 0.457 and serum levels are also increased during active inflammation [58] making this marker not a good candidate for a surrogate marker in clinical trials. …”
Section: Why Do We Have No Clinical Trials On the Prevention Of Intesmentioning
confidence: 99%